(untitled) (International Journal of Innovative Research in Computer Science & Technology, 2020)
The study investigated the effects of two modes of Computer Assisted Tutorial, Drill and Practice Instructional packages (CAI) on Pupils Achievement and Retention in English Language Spelling in Niger State. Findings show that CAI Tutorial, drill and practice packages mode strategy of instruction enhanced achievement and retention of English language spelling. The study adopted quasi–experimental design. Purposive sampling was used to select six schools from the seven educational zones in Niger State. The study sample comprised of 87 males and 93 females. Experimental groups were taught with CAI Tutorial, Drill and Practice packages while Control group was taught with lecture method. Six research questions and six hypotheses guided the study. English Language Achievement Test (ELAT) was used for data collection. The CAI packages and ELAT were face validated by experts while the reliability was established using Kuder Richardson (KR 20) analysis and the reliability coefficient was found to be r = 0.74. Mean and standard deviation were used to analyze the research questions while analysis of covariance (ANCOVA) was used in the testing of the hypotheses. It is recommended that, curriculum planners should infuse CAI packages into English language programmes so that primary school teachers’ can use it to teach English language concepts.